Fine specificity of autoantibodies to La/SSB: epitope mapping, and characterization - TZIOUFAS, A G (Blackwell Science Inc, 1997)
The B cell epitope mapping of La/SSB was performed using 20 mer synthetic peptides overlapping by eight amino acids covering the whole sequence of the protein. IgG, purified from sera of five patients with systemic lupus erythematosus (SLE) and four sera from patients with primary Sjögren's syndrome (pSS) were tested against the overlapping synthetic peptides. Peptides highly reactive with purified IgG were those spanning the regions 145–164, 289–308, 301–320 and 349–368 of the La protein. Determination of the minimum required length of the antigenic determinants disclosed the following epitopes:(147)HKAFKGSI(154), (291)NGNLQLRNKEVT(302), (301)VTWEVLEGEVEKEALKKI(318) and (349)GSGKGKVQFQGKKTKF(364). Predicted features and molecular similarities of the defined epitopes were investigated using protein databases. The La epitope (147)HKAFKGSI(154) presented 83.3% similarity with the (139)HKGFKGVD(146) region of human myelin basic protein (MBP) and 72% similarity with the fragment YKNFKGTI of human DNA topoisomerase II. Peptides corresponding to these sequences cross-reacted with anti-La/SSB antibodies. Sixty-three sera with anti-La/SSB antibodies from patients with pSS or SLE, 35 sera without anti-La/SSB antibodies from patients with SS or SLE and 41 sera from age/sex-matched healthy blood donors were tested against biotinylated synthetic epitope analogues in order to determine their sensitivity and specificity for the detection of anti-La/SSB antibodies. Anti-La/SSB were detected with various frequencies ranging from 20% to epitope (147)HKAFKGSI(154) to 100% to epitope (349)GSGKGKVQGKKTKF(364). The overall sensitivity and specificity using all assays with the synthetic peptides were found to be 93.6% and 85.6%, respectively. In conclusion, antibodies to La/SSB constitute a heterogeneous population, directed against different linear B cell epitopes of the molecule. The epitope (147)HKAFKGSI(154) presents molecular similarity with fragments of two other autoantigens, i.e. human MBP and DNA topoisomerase II. Finally, synthetic epitope analogues exhibit high sensitivity and specificity for the detection of anti-La/SSB antibodies.